Improving Zakat Management with SmartZiswaf: The Role of AI in Accountability and Fair Distribution - Prabowo, Yuga Bayu; Efendi, Fathan Rizki (Center of Strategic Studies (PUSKAS) BAZNAS, 2026)
PurposeThis study analyzes the role of the AI-based SmartZiswaf platform developed by BAZNAS in strengthening digital accountability, improving reporting transparency, and supporting equitable zakat distribution within Indonesia’s national zakat governance system. Design/Methodology/ApproachThe study uses a qualitative descriptive approach with a case study method. It relies on secondary data from official BAZNAS publications, annual reports, zakat outlook documents, national zakat policies, and relevant academic literature published between 2021 and 2024. The analysis applies content analysis and thematic analysis to identify key governance and accountability patterns. FindingsThe findings show that SmartZiswaf improves administrative efficiency and transparency through real-time digital reporting. AI integration supports data verification, minimizes duplication of beneficiary records, and enables more systematic monitoring of zakat fund flows. These functions contribute to stronger digital accountability and a more structured approach to equitable zakat distribution. Research limitations/implicationsThe study relies on secondary data and focuses on a single institutional case. Future research should include primary data, such as interviews and user-level analysis, and conduct comparative studies across zakat institutions to assess broader governance impacts. Practical implicationsThe results provide insights for zakat institutions and policymakers on how AI-based digital platforms can strengthen governance, reporting systems, and distribution mechanisms. The SmartZiswaf model can serve as a reference for digital transformation in zakat management. Social implicationsImproved digital accountability and transparency can increase public trust in zakat institutions and support fairer distribution of zakat funds, which contributes to poverty alleviation and social welfare. Originality/valueThis study offers an institutional-level analysis of AI-supported zakat governance in Indonesia and contributes to the limited literature on digital accountability in zakat management through the use of an integrated AI-based platform.